(untitled) (Itinera, 2024)
In this paper, George P. Pefanis discusses the presence of animals on stage from the perspective of French philosopher Jean Baudrillard. Baudrillard examines animality in relation to reason and the division between humans and non-humans. He presents four broad categories based on their relationship to humans. This article analyses the Baudrillardian concept of ‘somatisation’, which includes both the corporeality and physical vulnerability of animals, as well as certain psychic traits. The article explores the sentimentality projected onto animals and the implied superiority of humans in such sentimentality. Additionally, it enquires how the principles of ‘love for animals’ can be integrated into a performance featuring animals on stage from an ethical and ontological perspective. To support this discussion, the paper examines two examples of performances: ‘Embracing Animal’ by American artist Kathy High and ‘The Other’ by American artist Rachel Rosenthal.